Analisis Yuridis Hak Ex Officio Hakim Dalam Perkara Cerai Gugat : (Studi Kasus Putusan Pengadilan Agama Martapura Nomor 318/Pdt.G/2020/PA.Mtp) - Ahmad Syarif Fuadi; Dadin Eka Saputra; Munajah Munajah (Scholar Center, 2020)
Article 41 the law number 1 of 1974 aboutthe marriages set due to a divorce followed accordingly good cerai talak and divorce And cerai gugat.Article 149 compilation of laws the faith in its specially regulate about the consequences law divorce initiated by husbands (divorce).Based on article 149 a compilation of islamic law are mostly the judges are not punish husband to give waiting period then divorce and a living. However, in the verdict of case no. 318/Pdt.G/2020/PA. Mtp, The Panel of Judges adjudicates the verdict of the divorce case usinghis ex officio rights But in number do 318 / pdt.g / 2020 / pa.mtp, the judge in judge cerai gugat do the right use his ex officio to a defendant and to punish to pay a living waiting period and then divorce even though the plaintiff ( the wife ) do not ask this and the defendantnever attended the trial.This paper aims to find out how the judge considers the giving of mutah and iddah living in the divorce case and know how the juridical analysis of the verdict of the case. Methodology to be used that isnormative juridical to the doctrines of law with the approach statutory and conceptual approach then were analysed qualitatively juridical so as to give the answer on the matter.As for the result of analisanya among other: 1 ) the application of the right ex officio judge by punishing husband to pay then divorce and a living to former wife about the matters of 318 / pdt.g / 2020 / pa.mtp have been in line based on theprovisions of article 41 letters ( c of law no. 11/1974 jo article 149 letter a compilation of islamic law nevertheless the judge handed down the verdict exceeding what was demanded so as to deviate the provisions stipulated in Article 178 paragraph (3) HIR / Article 189paragraph (3) RBg and violates the principle of ultra petita. 2) The dropping of amar verdict with the charges against the defendantto pay a living waiting period, and a living children then divorce of incurring liability to the defendant a living waiting period, and a living children then divorce of incurring liability to the defendant should consider the presence of an ex-husband and the ability of a decent life and needs of the defendant as the principle of the audi alteram partem in article 4, clause 1 ) of law number 48 of 2009 about judicial power; So that is serving australians a judgment of not can be exercised (illusoir).